TRADE RELATIONS BETWEEN THE SOVIET UNION AND THAILAND: DOCUMENTARY EVIDENCE FROM THE NATIONAL ARCHIVES AND RECORDS ADMINISTRATION (NARA) FROM THE 1940S TO THE 1960S - Wiphatthanananthakul, Chanyapat (CRMA Journal of Humanities and Social Sciences, 2020)
The objectives of the article are to use documentary evidence to describe the economic and trade relations between “the Soviet Union” or the Union of Soviet Socialist Republics (USSR) and “Siam” or the Kingdom of Thailand, and analyze these relations from the perspective of the United States of America from the 1940s to 1960s. This documentary evidence was obtained from the National Archives and Records Administration (NARA), College Park, Maryland, United States of America in 2016 where the records are maintained and published legally. The evidence were examined and showed trade relations and issues chronologically in multiple dimensions from the US that are reflective of today’s circumstances and which can be adapted for use in the present day, especially in aspects of development diplomacy and socialism.